A method for selectively separating useful elements from anatase
The separation of aluminum and scandium through mechanical activation and nitric acid pressurized leaching method, and the leaching of iron hydrochloric acid, combined with the method of melt roasting-water leaching of titanium, the problem of long process flow and difficulty in multi-element separation in the recycling and utilization of deposition anatase resources is solved. , achieving efficient comprehensive resource recycling and product purity improvement.
Patent Information
- Application Number
- CN202310505508.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-06
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-05-06
AI Technical Summary
In the prior art, the resource recycling and utilization of deposition anatase has problems such as long process flow, difficulty in separation of multiple elements in the leaching solution, and low overall recovery rate.
Mechanical activation and nitric acid pressurized leaching method are used to selectively separate aluminum and scandium, followed by hydrochloric acid leaching, and finally titanium is extracted by melting and calcining-water leaching, and titanium is extracted by melting potassium bisulfate, and potassium bisulfate is recycled to reduce the consumption of auxiliary materials.
It realizes efficient selective separation and comprehensive recycling of aluminum, scandium, iron, titanium and silicon, improves resource utilization and product purity, simplifies the process flow, and reduces costs.
Smart Images

Figure CN116497229B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of comprehensive recycling of titanium-containing resources, and in particular to a method for selectively separating useful elements from anatase. Background Art
[0002] Titanium is a widely used metal material, mainly obtained from titanium-containing ores through beneficiation and smelting. Titanium-containing ores can be roughly divided into magmatic ores, sedimentary ores, metamorphic ores, residual ores and placer ores according to their different genesis. Sedimentary anatase has the characteristics of fine mineral distribution and complex associated elements due to its unique genesis. The beneficiation and smelting of sedimentary anatase is difficult, and a set of technical solutions with high resource utilization and good economic benefits has not yet been formed.
[0003] In a paper titled "Discussion on Chemical Ore Dressing Technology of a Sedimentary Titanium Ore in Sichuan", Jiang Peng et al. studied the recycling of sedimentary anatase and compared the two processes of sulfuric acid roasting-water leaching and roasting-sulfuric acid leaching. The final leaching rates of aluminum, iron and titanium in the leachate reached 90%, 90% and 80%, respectively, achieving the expected results. However, this process dissolves all the valuable metal elements in the liquid, and later faced the problem of separation of the elements, making the entire process relatively long.
[0004] In other public information, there are no reports on the comprehensive recycling and utilization of sedimentary rutile resources. Summary of the invention
[0005] In view of the problems in the prior art of recovering metals from anatase, such as long process flow, difficulty in separating multiple elements in the leaching solution, and low comprehensive recovery rate, the present invention provides a method for selectively separating aluminum, scandium, iron, titanium and silicon in anatase. According to the differences in the properties of different mineral phases in the ore, the method can achieve selective separation and comprehensive recovery of aluminum, scandium, iron, titanium, silicon and other elements in anatase, which not only has high comprehensive resource utilization rate and high product purity, but also has the advantages of short process flow and good economic benefits.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0007] A method for selectively separating useful elements from anatase, comprising:
[0008] Step S1, anatase is successively subjected to mechanical activation and nitric acid pressure leaching, followed by solid-liquid separation to obtain a scandium-containing aluminum liquid and a first filter material, and the scandium-containing aluminum liquid is subjected to neutralization extraction and stripping to obtain an aluminum liquid and a scandium-rich material; mechanical activation is used to improve the reaction activity of anatase, and the leaching of aluminum and scandium is improved. At the same time, nitric acid is used to selectively leach aluminum and scandium. The iron content in the leachate is low, and the selectivity and separation effect of extracting scandium are improved.
[0009] Step S2, adding hydrochloric acid solution to the first filter material to leach iron, and obtaining ferric chloride solution and the second filter material after solid-liquid separation; the main elements in the second filter material are silicon and titanium; using hydrochloric acid to leach iron, separating a relatively pure ferric chloride solution, which can be sold as a product.
[0010] Step S3, the second filter material is mixed with potassium hydrogen sulfate for melt roasting and water immersion, and then solid-liquid separation is performed to obtain a first filtrate and active silicon powder. After the first filtrate is hydrolyzed at high temperature, solid-liquid separation is performed to obtain titanium dioxide and a second filtrate; potassium hydrogen sulfate is added for melting titanium extraction, which has a better leaching effect than the sulfuric acid method for titanium extraction, and the potassium hydrogen sulfate can be recycled to reduce the consumption of auxiliary materials.
[0011] Step S4, mixing the second filtrate with sulfuric acid, evaporating and concentrating it, and cooling and crystallizing it to obtain potassium hydrogen sulfate, and the potassium hydrogen sulfate is returned to step S3.
[0012] Optionally, in step S1, the anatase ore is a sedimentary scandium-containing anatase ore, and the mass content of its main elements is: TiO2: 5.0%~7.0%, Al2O3: 20%~30%, TFe (total iron content): 15.0%~20.0%, SiO2: 25%~30%, MgO: 1.0%~1.5%, CaO: 0.1%~0.5%, MnO: 0.1%~0.2%, V2O5: 0.1%~0.2%, Sc2O3: 40~60g / t.
[0013] Optionally, in step S1, the anatase is mechanically activated by at least one of a disc mill, a ball mill and a rod mill, and after mechanical activation, the anatase fineness is -325 mesh, accounting for more than 95wt%.
[0014] Optionally, in step S1, the nitric acid pressure leaching conditions are: nitric acid concentration 20wt% to 35wt%, leaching liquid-solid mass ratio 2:1 to 4:1, leaching time 2h to 5h, and leaching temperature 150°C to 220°C.
[0015] Optionally, in step S1, the scandium-containing aluminum liquid is extracted using a mixed extractant of P204 and TBP, the raffinate is the aluminum liquid, and the inorganic phase of the organic phase extract is a scandium-rich material after NaOH back-extraction.
[0016] Optionally, in step S2, the conditions for leaching iron with hydrochloric acid are: hydrochloric acid concentration 10% to 30wt%, leaching liquid-solid ratio 2:1 to 4:1, leaching time 0.5h to 2h, and leaching temperature 80°C to 100°C.
[0017] Optionally, in step S3, the equipment used for melt roasting to extract titanium is a vacuum furnace, and the conditions are: the amount of potassium bisulfate added is 2 to 3 times (molar mass) the titanium dioxide content in anatase, the roasting temperature is 400 to 800°C, the roasting time is 2h to 4h, and after roasting is completed, it is naturally cooled to room temperature.
[0018] Optionally, in step S3, the calcined material needs to be ground to -325 mesh accounting for more than 90% before water immersion, and the water immersion conditions are: leaching temperature 10-30°C, leaching time 1h-3h, and leaching liquid-solid mass ratio 2:1-4:1.
[0019] Optionally, the active silicon powder has a high content of effective silicon and can be used for preparing fertilizers, building materials and water treatment.
[0020] Optionally, in step S3, the evaporation concentration needs to be carried out by adding 0.5 to 0.6 times (molar mass) of sulfuric acid.
[0021] The beneficial effects brought about by the technical solution provided by the present invention include at least:
[0022] 1) The present invention makes full use of the differences in the properties of different mineral phases in the ore and adopts different leaching agents to achieve step-by-step selective separation of multi-metal elements. In step S1, aluminum and scandium are separated, and the combined leaching rate of iron, titanium and silicon is less than 0.5%; in step S2, iron is separated, and the leaching rates of titanium and silicon are less than 0.1%; in step S3, titanium is separated, and the leaching rate of silicon is less than 0.1%.
[0023] 2) The silicon-containing mineral phase in the ore is treated by mechanical activation, pressurized nitric acid leaching, roasting and mixing. It has a high content of effective silicon and can be used in the preparation of fertilizers, building materials, water treatment and other industries, and has a wide range of uses.
[0024] 3) The utilization rate of each element in the ore is high. In the step S1 nitric acid pressure leaching, the leaching rates of aluminum and scandium reach 93% and 98% or more respectively; in the step S2 hydrochloric acid leaching of iron, the leaching rate of iron can reach more than 98%; in the step S3 melt roasting-water leaching of titanium, the leaching rate of titanium can reach more than 95%.
[0025] 4) Using potassium bisulfate for molten titanium extraction not only increases the titanium leaching rate, but also allows the potassium bisulfate to be reused. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0027] Figure 1The present invention is a process flow chart of the method for selectively separating aluminum, scandium, iron, titanium and silicon from anatase. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solution and advantages of the present invention more clear, the technical solution of the present invention will be described in detail below with reference to the accompanying drawings and specific embodiments.
[0029] The main element contents of the rutile used in the comparative examples and embodiments are: TiO2: 5.4%, Al2O3: 23.6%, TFe: 16.8%, SiO2: 28.3%, MgO: 1.3%, CaO: 0.27%, MnO: 0.16%, V2O5: 0.11%, Sc2O3: 45.5 g / t.
[0030] Comparative Example 1
[0031] S1. Take 100g of anatase with an average particle size of 0.1mm after coarse crushing and pour it into a disc mill for mechanical activation for 6min (the fineness of anatase after activation is -325 mesh, accounting for 95%), then pour 100g of activated anatase and 400g of 20% hydrochloric acid into a beaker, set the reaction temperature to 80℃, the reaction time to 4h, pour out the slurry after the reaction, separate the solid and liquid, and obtain the filtrate and filter residue. The aluminum content in the filtrate is 15.41g / L, the scandium content is 0.003g / L, and the iron content is 45.5g / L. The leaching rates of aluminum and scandium are 70.1%, 85.2%, and 89.65%, respectively. Direct leaching with hydrochloric acid did not achieve the purpose of selective separation of aluminum, iron, and scandium, and the next step of the experiment was not carried out.
[0032] Comparative Example 2
[0033] S1. Take 100g of anatase with an average particle size of 0.1mm after coarse crushing and pour it into a disc mill for mechanical activation for 6min (the fineness of anatase after activation is -325 mesh, accounting for 95%), then pour 100g of activated anatase and 400g of 30% sulfuric acid into a beaker, set the reaction temperature to 120℃, the reaction time to 4h, pour out the slurry after the reaction, separate the solid and liquid, and obtain the filtrate and filter residue. The aluminum content in the filtrate is 20.41g / L, the scandium content is 0.003g / L, the iron content is 45.5g / L, and the titanium content is 8.21g / L. The leaching rates of aluminum, scandium, iron, and titanium are 87.21%, 84.51%, 90.65%, and 74.11%, respectively. The use of sulfuric acid pressure leaching did not achieve the purpose of selective separation of aluminum, scandium, iron, and titanium, and the next step of the experiment was not carried out.
[0034] Comparative Example 3
[0035] S1. Take 100g of anatase with an average particle size of 0.1mm after coarse crushing and pour it into a disc mill for mechanical activation for 3min (the fineness of anatase after activation is -200 mesh, accounting for 95%), then pour 100g of activated anatase and 400g of 20% concentration nitric acid into a pressure reactor, set the reaction temperature to 180℃ and the reaction time to 4h, pour out the slurry after the reaction to separate the solid and liquid, and obtain the filtrate and filter material 1. The aluminum content in the filtrate is 15.41g / L, the scandium content is 0.003g / L, and the aluminum and scandium leaching rates are 70.1% and 85.2%, respectively. The aluminum and scandium leaching rates did not reach the expected effect, and the next experiment was not carried out. It shows that when the fineness of the anatase after activation does not meet the conditions, the useful elements in the anatase cannot be recovered.
[0036] Comparative Example 4
[0037] S1, take 100g of anatase with an average particle size of 0.1mm after coarse crushing and pour it into a disc mill for mechanical activation for 5min (the fineness of anatase after activation is -325 mesh, accounting for 95%), then pour 100g of activated anatase and 400g of 30% concentration nitric acid into a pressure reactor, set the reaction temperature to 180℃, the reaction time to 4h, pour out the slurry after the reaction, separate the solid and liquid, and obtain filtrate and filter material 1. The aluminum content in the filtrate is 27.42g / L, the scandium content is 0.004g / L, and the aluminum and scandium leaching rates are 94.5% and 98.4%, respectively. The filtrate is extracted with P204+TBP, and the organic phase is stripped with sodium hydroxide solution to obtain a scandium enriched material with a scandium content of 0.5%.
[0038] S2. Add 200 g of 20% hydrochloric acid to the filter material 1 obtained in step S1, with a leaching liquid-solid mass ratio of 2.3:1, and react for 2 h at 30°C. After the reaction, obtain filtrate and filter material 2. The iron content in the filtrate is 25 g / L, and the iron leaching rate is only 82%. The iron leaching rate did not meet expectations, so the next step of the experiment was not carried out.
[0039] Comparative Example 5
[0040] S1, take 100g of anatase with an average particle size of 0.1mm after coarse crushing and pour it into a disc mill for mechanical activation for 5min (the fineness of anatase after activation is -325 mesh, accounting for 95%), then pour 100g of activated anatase and 400g of 30% concentration nitric acid into a pressure reactor, set the reaction temperature to 180℃, the reaction time to 4h, pour out the slurry after the reaction, separate the solid and liquid, and obtain filtrate and filter material 1. The aluminum content in the filtrate is 26.55g / L, the scandium content is 0.0038g / L, and the aluminum and scandium leaching rates are 94.11% and 97.93%, respectively. The filtrate is extracted with P204+TBP, and the organic phase is stripped with sodium hydroxide solution to obtain a scandium enriched material with a scandium content of 0.6%.
[0041] S2. Add 200 g of 30% hydrochloric acid to the filter material 1 obtained in step S1, with a leaching liquid-solid mass ratio of 2.3:1, and react at 80°C for 2 h. After the reaction, obtain a filtrate and filter material 2. The iron content in the filtrate is 65 g / L, and the iron leaching rate is 96%.
[0042] S3. According to step S2, 2.5 times the molar mass of the titanium content in the filter material 2 obtained is directly mixed and added with 30 g of potassium hydrogen sulfate, and the mixture is roasted at 300°C for 2 h. After the roasting, the material is poured into 400 ml of water while hot for leaching for 2 h. After the leaching, the solid-liquid separation is performed to obtain filtrate 1 and filter material. The titanium content in filtrate 1 is 2 g / L, and the titanium leaching rate is only 10.1%. The titanium leaching rate did not meet expectations, and the next step of the experiment was not carried out.
[0043] Example 1
[0044] S1, take 100g of anatase with an average particle size of 0.1mm after coarse crushing and pour it into a disc mill for mechanical activation for 5min (the fineness of anatase after activation is -325 mesh, accounting for 95%), then pour 100g of activated anatase and 400g of 30% concentration nitric acid into a pressure reactor, set the reaction temperature to 180℃, the reaction time to 4h, pour out the slurry after the reaction, separate the solid and liquid, and obtain filtrate and filter material 1. The aluminum content in the filtrate is 26.55g / L, the scandium content is 0.0038g / L, and the aluminum and scandium leaching rates are 94.11% and 97.93%, respectively. The filtrate is extracted with P204+TBP, and the organic phase is stripped with sodium hydroxide solution to obtain a scandium enriched material with a scandium content of 0.6%.
[0045] S2. Add 200 g of 30% hydrochloric acid to the filter material 1 obtained in step S1, with a leaching liquid-solid mass ratio of 2.3:1, and react at 80°C for 2 h. After the reaction, obtain a filtrate and filter material 2. The iron content in the filtrate is 65 g / L, and the iron leaching rate is 96%.
[0046] S3. According to step S2, 2.5 times the molar mass of the titanium content in the filter material 2 obtained is directly mixed and added with 30g of potassium hydrogen sulfate, and the mixture is calcined at 500°C for 2h. After the calcined material is naturally cooled to room temperature, it is ground to a material fineness of -325 mesh accounting for 90%, and then mixed with 200ml of water and leached at 25°C for 1h. After the reaction is completed, the slurry is poured out for solid-liquid separation to obtain filtrate 1 and filter residue. The titanium content in filtrate 1 is 12.56g / L, and the titanium leaching rate is 94.21%; the silicon content in the filter residue is 41.23%. The filtrate 1 is hydrolyzed at 100°C for 1h, and then solid-liquid separation is performed to obtain filtrate 2 and filter material. The obtained filter material is titanium dioxide with a content of 98.5%.
[0047] S4. Add 25 g of 98% sulfuric acid to the filtrate 3 in step S3, and then evaporate and concentrate, cool and crystallize to obtain potassium hydrogen sulfate with a purity of 98%.
[0048] Example 2
[0049] S1, take 100g of anatase with an average particle size of 0.1mm after coarse crushing and pour it into a disc mill for mechanical activation for 5min (the fineness of anatase after activation is -325 mesh, accounting for 95%), then pour 100g of activated anatase and 300g of 30% concentration nitric acid into a pressure reactor, set the reaction temperature to 180℃, the reaction time to 4h, pour out the slurry after the reaction, separate the solid and liquid, and obtain filtrate and filter material 1. The aluminum content in the filtrate is 23.55g / L, the scandium content is 0.0038g / L, and the aluminum and scandium leaching rates are 89.45% and 90.61%, respectively. The filtrate is extracted with P204+TBP, and the organic phase is stripped with sodium hydroxide solution to obtain a scandium enriched material with a scandium content of 0.55%.
[0050] S2. Add 200 g of 30% hydrochloric acid to the filter material 1 obtained in step S1, with a leaching liquid-to-solid mass ratio of 2.3:1, and react at 80°C for 2 h. After the reaction, obtain a filtrate and filter material 2. The iron content in the filtrate is 63.51 g / L, and the iron leaching rate is 94.57%.
[0051] S3, according to step S2, the titanium content in the filter material 2 is directly mixed with 25g of potassium hydrogen sulfate, and roasted at 500℃ for 2h. After the roasted material is naturally cooled to room temperature, it is ground to a material fineness of -325 mesh accounting for 90%, and then mixed with 200ml of water and leached at 25℃ for 1h. After the reaction is completed, the slurry is poured out for solid-liquid separation to obtain filtrate 1 and filter residue. The titanium content in filtrate 1 is 11.25g / L, and the titanium leaching rate is 91.21%. The silicon content in the filter residue is 40.55%. The filtrate 1 is hydrolyzed at 120℃ for 1h, and then solid-liquid separation is performed to obtain filtrate 2 and filter material. The obtained filter material is titanium dioxide with a content of 99.10%.
[0052] S4. Add 25 g of 98% sulfuric acid to the filtrate 3 in step S3, and then evaporate and concentrate, cool and crystallize to obtain potassium hydrogen sulfate with a purity of 98.5%.
[0053] Example 3
[0054] S1, take 100g of anatase with an average particle size of 0.1mm after coarse crushing and pour it into a disc mill for mechanical activation for 5min (the fineness of anatase after activation is -325 mesh, accounting for 95%), then pour 100g of activated anatase and 400g of 30% concentration nitric acid into a pressure reactor, set the reaction temperature to 180℃, the reaction time to 4h, pour out the slurry after the reaction, separate the solid and liquid, and obtain filtrate and filter material 1. The aluminum content in the filtrate is 27.11g / L, the scandium content is 0.0039g / L, and the aluminum and scandium leaching rates are 95.05% and 99.3%, respectively. The filtrate is extracted with P204+TBP, and the organic phase is stripped with sodium hydroxide solution to obtain a scandium enriched material with a scandium content of 0.58%.
[0055] S2. Add 200 g of 30% hydrochloric acid to the filter material 1 obtained in step S1, with a leaching liquid-solid mass ratio of 2.3:1, and react at 90°C for 2 h. After the reaction, obtain a filtrate and filter material 2. The iron content in the filtrate is 72 g / L, and the iron leaching rate is 99.1%.
[0056] S3. According to step S2, 2.5 times the molar mass of the titanium content in the filter material 2 obtained is directly mixed and added with 30g of potassium hydrogen sulfate, and the mixture is calcined at 600°C for 2h. After the calcined material is naturally cooled to room temperature, it is ground to a material fineness of -325 mesh accounting for 90%, and then mixed with 200ml of water and leached at 25°C for 1h. After the reaction is completed, the slurry is poured out for solid-liquid separation to obtain filtrate 1 and filter residue. The titanium content in filtrate 1 is 15.01g / L, and the titanium leaching rate is 95.34%; the silicon content in the filter residue is 43.11%. The filtrate 1 is hydrolyzed at 100°C for 1h, and then solid-liquid separation is performed to obtain filtrate 2 and filter material. The obtained filter material is titanium dioxide with a content of 99.10%.
[0057] S4. Add 25 g of 98% sulfuric acid to the filtrate 3 in step S3, and then evaporate and concentrate, cool and crystallize to obtain potassium hydrogen sulfate with a purity of 98%.
[0058] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for selectively separating useful elements from anatase, characterized in that: include: Step S1, anatase is successively subjected to mechanical activation and nitric acid pressure leaching, followed by solid-liquid separation to obtain scandium-containing aluminum liquid and a first filter material, and the scandium-containing aluminum liquid is subjected to neutralization extraction and stripping to obtain aluminum liquid and scandium-rich material; Step S2, adding hydrochloric acid solution to the first filter material to leach iron, and obtaining ferric chloride solution and a second filter material after solid-liquid separation; the main elements in the second filter material are silicon and titanium; Step S3, melting and roasting the second filter material with potassium hydrogen sulfate, soaking it in water, and then performing solid-liquid separation to obtain a first filtrate and active silicon powder. After the first filtrate is hydrolyzed at high temperature, solid-liquid separation is performed to obtain titanium dioxide and a second filtrate; Step S4, mixing the second filtrate with sulfuric acid, evaporating and concentrating it, and cooling and crystallizing it to obtain potassium hydrogen sulfate, and the potassium hydrogen sulfate is returned to step S3; In step S1, the anatase is mechanically activated by at least one of a disc mill, a ball mill, and a rod mill, and after mechanical activation, the anatase fineness is -325 mesh, accounting for more than 95%; In step S1, the nitric acid pressure leaching conditions are: nitric acid concentration 20% to 35%, leaching liquid-solid ratio 2:1 to 4:1, leaching time 2h to 5h, leaching temperature 150° C. to 220° C.; In step S2, the conditions for leaching iron with hydrochloric acid are: hydrochloric acid concentration 10% to 30%, leaching liquid-solid ratio 2:1 to 4:1, leaching time 0.5h to 2h, leaching temperature 80°C to 100°C; In step S3, the equipment used for melt roasting titanium extraction is a vacuum furnace, and the conditions are: the amount of potassium bisulfate added is 2 to 3 times the titanium dioxide content in anatase, the roasting temperature is 400 to 800°C, the roasting time is 2h to 4h, and after roasting is completed, it is naturally cooled to room temperature.
2. The method according to claim 1, characterized in that In step S1, the anatase is a sedimentary scandium-containing anatase ore, and its main element mass content is: TiO2: 5.0% ~ 7.0%, Al2O3: 20% ~ 30%, TFe: 15.0% ~ 20.0%, SiO2: 25% ~ 30%, MgO: 1.0% ~ 1.5%, CaO: 0.1% ~ 0.5%, MnO: 0.1% ~ 0.2%, V2O5: 0.1% ~ 0.2%, Sc2O3: 40 ~ 60g / t.
3. The method according to claim 1, characterized in that In step S1, the scandium-containing aluminum liquid is extracted using a mixed extractant of P204 and TBP, the raffinate is aluminum liquid, and the inorganic phase of the organic phase extract is a scandium-rich material after NaOH back extraction.
4. The method according to claim 1, characterized in that: In step S3, before water immersion, the calcined material needs to be ground to -325 mesh accounting for more than 90%, and the water immersion conditions are: leaching temperature 10-30°C, leaching time 1h-3h, and leaching liquid-solid ratio 2:1-4:
1.
5. The method according to claim 1, characterized in that The active silicon powder has a high content of effective silicon and can be used for preparing fertilizers, building materials and water treatment.
6. The method according to claim 1, characterized in that In step S3, the evaporation concentration needs to be carried out by adding 0.5 to 0.6 times of sulfuric acid.
Citation Information
Patent Citations
Method for purifying quartz sand by molten salt method
CN102249249A
Method for enriching scandium in anatase raw ore
CN103667749A
Method for selectively leaching titanium from titaniferous slag
CN110453093A
Titanium ore comprehensive utilization process
CN111747436A
Direct leaching process for titanium recovered sulfuric acid
CN111748701A
